2011
DOI: 10.1155/2011/765473
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sleeve Gastrectomy on NASH and Type 2 Diabetes Mellitus

Abstract: Background. Nonalcoholic fatty liver disease is present in up to 85% of adipose patients and may proceed to nonalcoholic steatohepatitis (NASH). With insulin resistance and obesity being the main risk factors for NASH, the effect of isolated sleeve gastrectomy (ISG) on these parameters was examined. Methods. 236 patients underwent ISG with intraoperative liver biopsy from December 2002 to September 2009. Besides demographic data, pre-operative weight/BMI, HbA1c, AST, ALT, triglycerides, HDL and LDL levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…[115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133] A schematic representation of the search in the online databases and the identification, exclusion and selection of the articles is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133] A schematic representation of the search in the online databases and the identification, exclusion and selection of the articles is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In an analysis on prospective data gathered from 236 individuals, Karcz et al 128 observed significant improvements in AST, ALT, triglycerides and high-density lipoprotein (HDL) levels one and three years after SG. NASH patients showed significant losses of body weight and amelioration of NASH status.…”
Section: Sleeve Gastrectomymentioning
confidence: 99%
“…NAFLD is becoming a prevalent chronic liver disease, due to the association with the ever-increasing rates of morbid obesity and metabolic syndrome. The rise is alarming, as the disease has been seen to cascade from steatohepatitis to fibrosis and liver cirrhosis and eventually even hepatocellular carcinoma [19]. NAFLD also increases the risk of multiple cardiac and metabolic diseases [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Karcz et al [19], the effect of LSG on NAFLD and diabetes was observed using an intra-operative liver biopsy and postoperative liver enzyme monitoring. An observation of significant NAFLD resolution was found, very much similar to this study, but this was solely based on an improvement in postoperative liver function test results.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported a resolution rate of 60-90% for diabetes after sleeve gastrectomy in the short term (6 months to 1 year) [40][41][42][43][44][45][46][47][48][49]. Other studies have reported inferior results for diabetes resolution [50][51][52][53].…”
Section: Vertical Sleeve Gastrectomymentioning
confidence: 99%